2006
DOI: 10.1001/archotol.132.11.1226
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Outcomes After Laser Resection of Early-Stage Glottic Cancer With Adjuvant Cryotherapy

Abstract: To evaluate the vocal outcomes of patients with early-stage glottic carcinoma undergoing laser resection with adjuvant cryoablative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Several investigators have reported a decreased incidence in web formation with the intraoperative application of mitomycin C 57,58 or with the use of cryotherapy just after the laser resection. 59 Tumors classified as T2 with posterior extension tend to have lower local control rates with transoral laser resection. 60 Tumors extending into Morgagni ventricle and supraglottic extension of glottic carcinoma (transglottic carcinoma) have a higher risk of thyroid cartilage invasion, especially for anteriorly or posteriorly extending tumors.…”
Section: Anterior Commissurementioning
confidence: 99%
“…Several investigators have reported a decreased incidence in web formation with the intraoperative application of mitomycin C 57,58 or with the use of cryotherapy just after the laser resection. 59 Tumors classified as T2 with posterior extension tend to have lower local control rates with transoral laser resection. 60 Tumors extending into Morgagni ventricle and supraglottic extension of glottic carcinoma (transglottic carcinoma) have a higher risk of thyroid cartilage invasion, especially for anteriorly or posteriorly extending tumors.…”
Section: Anterior Commissurementioning
confidence: 99%
“…41 The application of mitomycin C or cryotherapy intraoperatively after resection of anterior commissure tumors may also reduce granuloma and web formation. 42,43 No study has specifically evaluated voice outcomes in patients requiring a "secondlook" procedure (repeat TLM to ascertain margin status), but the study by Stone and colleagues 33 found a correlation between the number of TLM procedures and worse acoustic voice results. Repeat TLM resection may indeed increase the ultimate amount of tissue resected at the glottis and produce further scar tissue.…”
Section: What Are the Factors Involved In Voice Quality After Transormentioning
confidence: 99%
“…Videostroboscopy performed after treatment revealed a return of mucosal waves. Histological evaluation showed improved wound healing compared to controls including improved collagen organization and decreased keratinization 4. Strome et al also performed a retrospective study to evaluate vocal outcomes in patients treated with adjuvant cryotherapy after a laser resection of early glottic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the GI tract have demonstrated eradication of intramucosal carcinoma,1 effective treatment of human papillomavirus infection,2 and hemostasis3 providing for a submucosal injury without the potential for mechanical injury and normalization of the mucosa with a controlled wound response. Additionally, cryotherapy has also been used as adjuvant therapy in patients undergoing transoral resection of early glottic cancers and has been shown to improve voice quality in these patients 4. These findings, combined with the breadth of evidence regarding cryotherapy in dermatology and other fields, suggest that treatment with spray cryotherapy may be an appropriate modality for primary or adjunctive treatment of glottic and subglottic stenosis to modify the wound response, and when appropriate, combined with balloon dilation.…”
Section: Introductionmentioning
confidence: 99%